2013
DOI: 10.1111/1755-6724.12112
|View full text |Cite
|
Sign up to set email alerts
|

Further Information of the Associated Li Deposits in the No.6 Coal Seam at Jungar Coalfield, Inner Mongolia, Northern China

Abstract: Abstract:Total 138 coal samples and 14 parting samples were taken from the No. 6 Seam of the Jungar Coalfield, Inner Mongolia. These samples were analysed by optical microscopy, sequential chemical extraction procedure (SCEP), inductively coupled plasma mass spectrometry (ICP–MS), X–ray powder diffraction (XRD), and scanning electron microscope in conjunction with an energy–dispersive X–ray spectrometer (SEM–EDX) analysis. The results indicate that the Li contents have reached the industrial grade of the coal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…Due to the potential economic value, the issue of investigating the mode of occurrence of Li has become an urgent topic worldwide. Earlier studies have suggested that Li can occur both in inorganic and organic matter in coals [9,32,33,87], while other studies on the coals from the Jungar Basin indicated that Li is mainly associated with kaolinite/illite, chlorite, and boehmite [22,71,84]. However, Li mainly occurs in aluminosilicate minerals, such as kaolinite, in the coal from the Datong coalfield and Ningwu coalfield (adjacent to the Datong coalfield) [15,29].…”
Section: Lithiummentioning
confidence: 99%
See 4 more Smart Citations
“…Due to the potential economic value, the issue of investigating the mode of occurrence of Li has become an urgent topic worldwide. Earlier studies have suggested that Li can occur both in inorganic and organic matter in coals [9,32,33,87], while other studies on the coals from the Jungar Basin indicated that Li is mainly associated with kaolinite/illite, chlorite, and boehmite [22,71,84]. However, Li mainly occurs in aluminosilicate minerals, such as kaolinite, in the coal from the Datong coalfield and Ningwu coalfield (adjacent to the Datong coalfield) [15,29].…”
Section: Lithiummentioning
confidence: 99%
“…Numerous investigations on the elemental geochemistry in coals from north China have been carried out [7][8][9][10][11][12][13][14][15][16][17][18][19] and have revealed that various valuable elements can be found in high concentrations which gives them considerable economic significance [9,15,17,[20][21][22][23]. Dai et al [24] suggested that rare metals, such as REY, Cr, Ti, Li, Be, Au, Ag, Pt, Pd, etc., have high potential for industrial utilization in some Chinese coals.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations